2014
DOI: 10.1111/lasr.12060
|View full text |Cite
|
Sign up to set email alerts
|

Unfounding Sexual Assault: Examining the Decision to Unfound and Identifying False Reports

Abstract: One of the most controversial-and least understood-issues in the area of sexual violence is the prevalence of false reports of rape. Estimates of the rate of false reports vary widely, which reflects differences in way false reports are defined and in the methods that researchers use to identify them. We address this issue using a mixed methods approach that incorporates quantitative and qualitative data on sexual assault cases that were reported to the Los Angeles Police Department (LAPD) in 2008 and qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
103
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 23 publications
(67 reference statements)
2
103
1
2
Order By: Relevance
“…The new guidelines, however, can be expected to have led to more valid figures on the prevalence of false allegations of rape. A study by Spohn et al [19] does not seem to reject the validity of this hypothesis.…”
Section: The Unfound Category and The New Policymentioning
confidence: 82%
See 4 more Smart Citations
“…The new guidelines, however, can be expected to have led to more valid figures on the prevalence of false allegations of rape. A study by Spohn et al [19] does not seem to reject the validity of this hypothesis.…”
Section: The Unfound Category and The New Policymentioning
confidence: 82%
“…The researchers concluded that in 2.4% of all allegations of sexual assault that were classified by LAPD officers as unfounded evidence existed that a crime did occur. In 9.9% of unfounded allegations Spohn et al [19] concluded that there was evidence that complainants lacked interest to pursue the case or were motivated by fear or pressure to stop pursuing the case. Thus, a total of 12.3% of all allegations were deemed to be misclassified by the LAPD.…”
Section: The Unfound Category and The New Policymentioning
confidence: 99%
See 3 more Smart Citations